2010
DOI: 10.1097/hp.0b013e3181cd6536
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Diagnostic Exposure to Ionizing Radiation and Leukemia Risk Among German Uranium Miners

Abstract: Lung cancer is a well-known effect of radon exposure in uranium mines. However, little is known about the induction of leukemia by radiation exposure in mines. Moreover, miners usually have occupational medical checkup programs that include chest x-ray examinations. Therefore, the aim of the present study was to re-examine leukemia risk among miners, taking into account exposure to x rays for diagnostic purposes. The data used were from a previously analyzed individually matched case-control study of former ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
0
23
0
1
Order By: Relevance
“…An early pooled analysis of radon and leukemia among miners showed a positive association for miners in the first 10 years of employment (Standardized Mortality Ratio ¼1.93; 95% confidence interval (CI) ¼1.19-2.95) but no association overall and no association with cumulative exposure to radon (Darby et al, 1995). Some of the more recent mining cohort studies, however, found some evidence for an association between the highest radon exposure group (Möhner et al, 2010(Möhner et al, , 2006 or radon dose (Gillies and Haylock, 2014;Rericha et al, 2006) and leukemia incidence or mortality.…”
Section: Introductionmentioning
confidence: 92%
“…An early pooled analysis of radon and leukemia among miners showed a positive association for miners in the first 10 years of employment (Standardized Mortality Ratio ¼1.93; 95% confidence interval (CI) ¼1.19-2.95) but no association overall and no association with cumulative exposure to radon (Darby et al, 1995). Some of the more recent mining cohort studies, however, found some evidence for an association between the highest radon exposure group (Möhner et al, 2010(Möhner et al, , 2006 or radon dose (Gillies and Haylock, 2014;Rericha et al, 2006) and leukemia incidence or mortality.…”
Section: Introductionmentioning
confidence: 92%
“…In this study, data on the medical examinations are extracted from the medical archives. A case-control study on leukaemia incidence in WISMUT miners by Möhner et al 21 that included doses from medical exposure showed that the risk estimates based on occupational doses alone and those based on the sum of occupational and medical doses were similar.…”
Section: Discussionmentioning
confidence: 99%
“…The International Agency for Research on Cancer classifies radon as a human carcinogen 26 because of evidence of an association between radon and lung cancer summarized in the BEIR VI report. 27 Recent studies have suggested that other health outcomes such as leukemia 28,29 and cardiovascular disease 30,31 may also be linked to radon exposure, although results are equivocal. The average cumulative radon exposure estimated for the FMPC cohort (26 WLMs) is comparable to exposures (i.e., within a factor of 3) in some uranium miner studies reporting excess lung cancer risk.…”
Section: Discussionmentioning
confidence: 99%